Rethinking risk: a narrative approach - Felton, Anne; Stickley, Theodore (Emerald, 2018)
Purpose The assessment and management of risk is central to contemporary mental health practice. The emergence of recovery has contributed to demands for more service user centered approaches to risk. This paper examines the potential of narrative as a framework for understanding risk and safety in mental health care. Design/methodology/approach Narrative theory is adopted to structure a debate examining the potential role of a narrative approach to risk assessment and inform future practice. Findings There is a danger that even within services, people with mental health problems are understood in terms of their riskiness perpetuating an image of service users as ‘dangerous others’. This is confounded by a disconnection with individual context in the risk assessment process. Narrative centralizes the persons’ subjective experience and provides a contemporaneous self-account of their identity. This situates risk within a context and creates possibility for greater understanding of coping, strengths and resilience. Originality/value There has been a call for new ways of working with risk in mental health which facilitate safety and recovery. There is limited examination of what this might actually look like. This paper presents narrative as an approach that may achieve these aims.